Community Empowerment Through Optimizing Local Wisdom as a Support for The Value of Economic Life - Nur Hidayah; Syamsul Arifin; Devangga Putra Adhitya Pratama; Kurniawati; Andre Tandi Bamba Dominggus; Aprilia Asharifah Suprapto; Ayuni Nurcahyanti (TGO Journal of Community Development, 2023)
Community Service (PKM) is an annual program carried out by each university which is an application of the Higher Education Chess Dharma. While the Real Work Lecture (KKN) is an annual program carried out by each university which is an application of the Higher Education Chess Dharma. With the implementation of PKM and KKN, it provides extraordinary benefits for students and the community because the results obtained from the implementation of PKM and KKN are enormous, such as an experience gained by students in the form of how to live with the community properly and much more. The implementation of PKM and KKN with "Building Competitive Villages Based on Local Potential, Technology & Green Economy" is oriented towards community empowerment, aiming for students to be able to think critically, analyze problems carefully, and find the best solutions in dealing with various problems related to the scientific field theoretically and practically. From PKM and KKN activities, students are able to develop science, technology, and art in community life.